2021
DOI: 10.1177/21582440211022234
|View full text |Cite|
|
Sign up to set email alerts
|

The Other Side of the Coin: Perceptions of Twice-Exceptional Students by Their Close Friends

Abstract: Friendship can be critical at any age but considering the gifts and challenges of twice-exceptional students, friends can be an essential element in navigating school years. The purpose of this study was to explore the perceptions that close friends of twice-exceptional students have about their friendship, characteristics, and how they relate to classmates and teachers. The sample was comprised of 17 students. Under a qualitative design, in-depth interviews were conducted with friends of students who were gif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
(69 reference statements)
0
0
0
Order By: Relevance
“…A twice-exceptional child is defined as a child who is gifted but exhibits the presence of one or more handicapping conditions. This is what makes their giftedness seem like a condition covered by their disability (Klingner, 2022;Conejeros-Solar et al, 2021). The lack of understanding of the condition of twiceextraordinary students hinders teachers and parents from recognising and helping them to overcome their problems (Amran & Majid, 2019).…”
Section: Giftedness Of Twice-exceptionalmentioning
confidence: 99%
“…A twice-exceptional child is defined as a child who is gifted but exhibits the presence of one or more handicapping conditions. This is what makes their giftedness seem like a condition covered by their disability (Klingner, 2022;Conejeros-Solar et al, 2021). The lack of understanding of the condition of twiceextraordinary students hinders teachers and parents from recognising and helping them to overcome their problems (Amran & Majid, 2019).…”
Section: Giftedness Of Twice-exceptionalmentioning
confidence: 99%
“…Lee and Ritchotte [2] claim that the relative lack of understanding of twice exceptionality is a barrier to nurturing the students' talents. It might also lead to underachievement in school and to frustration [6,25], have negative effects on their socio-emotional well-being [20,21], and therefore lead to long-term negative outcomes for these individuals. Several studies have found that 2e students are vulnerable in psychological traits and often exhibit low-academic self-concept, low academic self-efficacy, and low self-esteem [14,20,26,27].…”
Section: Consequences Academic Achievement and Psychosocial Well-beingmentioning
confidence: 99%
“…Several studies have found that 2e students are vulnerable in psychological traits and often exhibit low-academic self-concept, low academic self-efficacy, and low self-esteem [14,20,26,27]. These vulnerabilities may cause the unreasonably high risk of academic failures of 2e students found in many studies [25,26]. Wang and Neihart [26] claim that the support and care from parents, teachers, and peers are important in order to reach a high academic self-efficacy for 2e students.…”
Section: Consequences Academic Achievement and Psychosocial Well-beingmentioning
confidence: 99%
See 2 more Smart Citations